Implementation of The Basic Freedom of Contract in Review From The Shariah Alliance - Ulfanora (Ekasakti Journal of Law and Justice, 2024)
In civil matters, the parties will not be separated from the legal relationship. The legal relationship itself arises when there are rights and obligations of the parties so that what is agreed can be achieved. The parties are given freedom to make a contract. The contract itself must meet both subjective and objective requirements. One of the subjective conditions, which is the agreement between the parties, must be based on the principle of freedom of contract. The basis of freedom of contract according to Article 1338 BW "All legally made agreements are legally binding on those who make them”. The purpose of Article 1338 BW is that the basis for the parties to carry out the contract must be equality, justice, honesty and truth. The meaning of freedom of contract does not mean that the law allows parties to deviate from legal regulations or immoral acts. The Draft Law or what is known as (RUU) Engagements is a draft sub-codification of the national engagement law which previously, sub-engagements were regulated in Book III BW/Perdata. A special codification of contract law regulates sharia contracts as a form of implementing cooperation or business agreements with sharia principles. Therefore, in this article the author will explore the principle of freedom of contract in sharia agreements in cooperation agreements between parties in society. This research is legal research (doctrinal research) with an analytical approach (analytical research), a statutory approach (statues approach), and a conceptual approach (conceptual approach). The formulation of the problem to be studied is as follows, first Basis of Freedom of Contract in Agreements, Second, Freedom of the parties in carrying out the agreement, and third, The application of the basic freedom of contract is reviewed from the sharia alliance. The results of the research explain firstly, freedom of contract in contractual relationships is the essence of individuals being able to carry out the agreements agreed to in the contract as long as they do not conflict with public order and legislation. Second, freedom of contract on a contract must be based on good faith (good faith) the parties and state their wishes (conduct) proportionally. Third, The application of freedom of contract in sharia agreements places greater emphasis on benefits for the benefit of the parties and is not merely individualistic.